From sensory impressions to revisit intention: Multisensory tourism experiences in East Java’s tourism villages - Soebandhi, Santirianingrum; Kristiningsih, Kristiningsih; Trimarjono, Adrianto; Ramiza Syahri, Aqila (Master of Management, Department of Management, Faculty of Business and Economics Universitas Islam Indonesia, 2026)
The increasing shift toward experiential tourism highlights the importance of understanding how sensory elements influence tourists’ perceptions and behavioral intentions, particularly in village-based destinations that emphasize authenticity and immersion. This study aims to examine the roles of sight, sound, taste, smell, and touch in shaping memorable tourism experiences and influencing revisit intention in tourism villages in East Java, Indonesia. The population of this study consisted of tourists who had visited selected tourism villages in East Java, and data were collected from 300 respondents using an online questionnaire. A purposive sampling technique was applied to select visitors who had experienced one of the identified tourism villages within the previous two years. The proposed relationships were analyzed using partial least squares structural equation modeling (PLS-SEM), including measurement model assessment to evaluate reliability and validity, followed by structural model evaluation and mediation analysis through bootstrapping. The findings indicate that auditory and tactile dimensions have the strongest influence on the formation of memorable tourism experiences, followed by visual and taste-related dimensions, while olfactory factors do not demonstrate a significant effect on either memorable tourism experiences or revisit intention. These results suggest that sensory elements involving stronger visitor engagement, particularly sound and touch through natural soundscapes, traditional music, and hands-on cultural activities, are more effective in creating lasting impressions, while visual and taste-related elements play a supportive role in shaping tourists’ overall experience. From a practical perspective, this study highlights the importance for destination managers and local tourism stakeholders to prioritize the development of sensory-rich offerings that emphasize sound and touch in order to enhance destination appeal and encourage repeat visits. Theoretically, this research contributes to the multisensory tourism literature by clarifying the relative importance of sensory dimensions in shaping meaningful tourism experiences within village-based and experience-oriented destinations.